Emissions factors from distributed, small-scale biomass gasification power generation: Comparison to open burning and large-scale biomass power generation. (1st March 2019) - Ahmed, Omar Y.; Ries, Matthew J.; Northrop, William F.
Abstract: Waste woody biomass is one of the most readily available yet underutilized renewable energy sources. Small quantities of wood waste in remote locations are often openly burned when they are not economical to transport and burn in large-scale facilities. Small-scale (10–100 kW) distributed gasifier-generator systems offer an alternative use for this biomass. In this work, we present emissions factors experimentally measured from a commercially available gasifier-generator system. Average emissions factors per mass of dry biomass with high quality producer gas were found to be 1.53 kg-CO2, 11.3 g-CO, 8.7 g-CH4, 2.4 g-NOx, and 0.01 g-soot per kg of feedstock. On an energy basis, emissions were 2.04 kg-CO2, 30.3 g-CO, 18.6 g-CH4, 5.0 g-NOx, and 0.02-g soot per kWh of electricity produced at a maximum load of 15 kW. Our research found that producer gas heating value is inversely proportional to both power output and biomass moisture content. Low quality producer gas was found to significantly increase CO, CH4 and soot emissions from the system but decrease NOx emissions. Small-scale biomass gasification emits less CO2, CO, and soot than open burning, but further improvements are required before emissions from small-scale systems are competitive with emissions from large-scale biomass power generation. Graphical abstract: Highlights: Small-scale biomass gasification emits less CO2, CO, and soot than open burning. Producer gas heating value decreases with increased power and moisture content. High moisture content producer gas increases CO, CH4 and soot but decreases NOx . Small-scale gasifiers emit less CO2 than large-scale plants by producing biochar.